A Review on Design Considerations and Connection Techniques in Modular Composite Construction - Manivannan Thulasirangan Lakshmidevi; K. S. K. Karthik Reddy; Riyadh Al-Ameri; Bidur Kafle (Applied Sciences)
Precast concrete structures have become increasingly popular in the construction industry due to their ability to enhance efficiency, structural soundness, quality, and sustainability. Among these, modular construction has emerged as a transformative approach that fully leverages precast technology by manufacturing 3D modules off-site and assembling them on-site using inter-module connections. This study reviewed current literature trends on precast concrete structures and modular construction, analysing how modular construction distinguishes itself from other precast systems. This review further emphasises the role of composite connections—grouted, bolted, and hybrid systems—critical in ensuring structural integrity, efficiency in load transfer, and seismic resilience in modular construction. Advancements in composite connections have demonstrated significant promise, particularly in seismic performance, with reported energy dissipation improvements of up to 30% in hybrid connection systems. Yet limitations still exist, necessitating improvements in load transfer efficiency, ductility, and reliability under dynamic loads. Additionally, design considerations for modular construction, such as modular configurations, handling stresses, and transportation challenges, are explored to highlight their influence on system performance. This review underscores the feasibility and potential of modular construction in fostering sustainable and resilient infrastructure, as studies indicate that modular construction can reduce project timelines by up to 50% while minimising material waste by approximately 30%. The role of Non-Destructive Evaluation (NDE) techniques and intelligent monitoring systems in assessing and enhancing the lifecycle performance of composite connections is also emphasised. This review further advocates for continued research to refine composite connections and support the broader adoption of modular construction in modern building practices.